Perbandingan Dialek Bahasa Jawa Pemalangan Desa Wanarejan Utara dan Desa Randudongkal Kabupaten Pemalang: Kajian Linguistik Kontrastif - Sagita, Yuni; Safitri, Dhewi; Putri Hardiasari, Shiva Arinda; Githa Sulistyawati, Tricya; Utom, Widzar (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
This study compares the phonology and lexicon of the Pemalang Javanese dialect as spoken by the communities in Wanarajen Utara and Randudongkal villages, located in Pemalang Regency, Central Java. Phonological and lexical analyses are employed to investigate the linguistic variations within the Pemalang Javanese dialect. Data collection was carried out using interviews, observation, and note-taking methods. The results are presented using a qualitative descriptive approach, providing accurate and factual descriptions through narrative explanations based on real-life observations in the research. In identifying the dialectal differences between the two villages, contrastive linguistics and geolinguistics methods were applied. The findings reveal several phonological and lexical differences influenced by factors such as topography, social interaction, and migration. For instance, the word for [tree] in Randudongkal is [wit] with the vowel /i/, while in Wanarajen Utara, it is pronounced as [wet] with the vowel /e/. Lexically, the word for [pants] differs between the two regions: Wanarajen Utara uses [suwal], whereas Randudongkal uses [katok]. This study provides insights into the dialectal variation within the Javanese language in Pemalang Regency and may serve as a reference for further studies on Javanese dialectology.